"Learning by design": what sports coaches can learn from video game designs - Robertson, S.; Woods, C. T. (Sports Medicine - Open, 2021)
There have been multiple calls made in the sport science literature for the promotion of interdisciplinarity to progress some of sports` most prevailing challenges. Designing practice environments that support learning represents one such challenge, particularly given contemporary perspectives of skill acquisition and motor learning calls for coaches to realign their role—progressing toward the designers of practice tasks that promote athlete-environment interactions. In doing so, performers learn through exploration, deepening a relationship with their performance environment as they solve problems based on changing and interacting constraints. This paper illustrates an interdisciplinary approach to the area of learning through sport practice by adapting established principles embedded in video game designs. Specifically, 13 principles common to good video game designs are described, with practical examples of each provided across different sports. Fundamentally, this paper aims to offer sports practitioners with an overview and application of key principles that could support learning by design. Beyond this, the ideas presented here should further illustrate the value of interdisciplinarity in sports research and practice.